Maintenance therapy promotes profound organ and haematologic response in light-chain amyloidosis patients not undergoing autologous stem cell transplantation - Wenjing Wang; Jing Li; Tianhong Xu; Yang Yang; Chenqi Yu; Pu Wang; Chi Zhou; Peng Liu (Annals of Medicine)
Background Evidence on maintenance therapy following frontline induction is sparse in primary light-chain amyloidosis (AL), especially for those who do not undergo autologous haematopoietic stem cell transplantation (ASCT).Methods We enrolled primary AL patients who achieved at least haematologic very good partial response (VGPR) by the 4th month at the frontline from December 2008 to June 2023 at Zhongshan Hospital, Fudan University. Those who followed maintenance therapy were identified as the maintenance group (n = 44), whereas those entering the observational phase were classified as the observational group (n = 24).Results After 7.2(interquartile range, 4.7–18.6) months of maintenance therapy, 9(20.5%), 14(31.8%) and 5 (11.4%) patients achieved improvement in haematologic, cardiac and renal response respectively. Five (11.4%) patients had minimal residual disease (MRD) response conversion from positive to negative based on maintenance therapy. In the observation group, none of the patients had haematologic response improvement, with 3(12.5%) and 1(4.2%) patient showing cardiac and renal response improvement during follow-up.Conclusion This study identified the clinical benefits of maintenance therapy in patients with AL who did not undergo ASCT in real-world practice.